A Novel Table Finite State Machine-Based Routing Algorithm Implementation - Ribeiro Carneiro, Cassiano; de Almeida Amazonas, José Roberto (INFOCOMP Journal of Computer Science, 2023)
State machine is a concept originally proposed for computational numerical systems and used for modeling systems with applications in several fields. Governed by its own logic, an input produces a change of state and an output on the machine. The routing by FSM technique uses this dynamic to generate numerical sequences that represent the network nodes and the routes through which data transmission is allowed. With this, the number of transmissions is reduced and, consequently, the energy consumption. Due to its low complexity, the technique is particularly interesting in the context of networks with limited resources, such as wireless sensor networks and nanodevice networks. In this work, we show that for several scenarios the technique becomes inefficient due to the large number of routes produced and we propose a new implementation whereby the packet size remains reduced for a wide range of routing parameters.